COGNITIVE DYSFUNCTION IN WOMEN AFTER THYROID SURGERY (Academicia Globe: Inderscience Research, 2023)
The state of cognitive function was studied in 23 middle-aged women in the postoperative period under general anesthesia. Of these, 12 had a history of uterine amputation. Postoperative cognitive dysfunction was detected in 8 patients, which is 66.7%, who had a history of obstetric surgery. All these patients had hypocalcemia. This study confirms the severe course and high prevalence of cognitive dysfunction in the postoperative period under general anesthesia after surgery in women with hypocalcemia.